Variation of Indigofera tinctoria’s Immersion Time on Dye Solution and its effect on DSSC efficiency - Fahru Nurosyid; Parahita Faqih; Zulaldi Yahya Dewangga; Nurdiyantoro Putra Prasetya (Department of Physics, Sebelas Maret University, 2020)
The utilization of Indigo tinctoria as a DSSC sensitizer has been done to study the effect of I. tinctoria’s immersion time on DSSC efficiency. One of the most essential components in DSSC is a sensitizer or dye. In this work, the dye has been used in DSSC is the natural indigo dye from I. tinctoria leaves. The extraction was done by dissolving 50 grams of I. tinctoria leaves in 500 mililiters aquades and soaking in various time: 12, 24, 36, and 48 hours. The optical properties of dye solution was characterized by UV-Vis spectrophotometer and the current-voltage of DSSC was characterized by Keithley I-V Meter. The highest absorbance is 2.7 of 48h dye solution, but the best efficiency of DSSC is 5.39 x 10-3 % that owned 24 h cell.